혈액투석 환자의 약물복용 이행도 및 이행 영향요인: 1차, 2차 의료기관 중심 - 서연희; Yon Hee Seo; 임순옥; Sun Og Lim; 현은희; Eun Hee Hyeon; 김혜원; Hae Won Kim; 엄미란; Mi Ran Eom (Perspectives in nursing science, 2015)
Purpose: The purpose of this study was to identify the factors influencing medication adherence in hemodialysis patients among primary medical care and secondary medical care. Methods: A cross-sectional survey design was utilized. Data were collected using questionnaires from 280 hemodialysis patients who had taken prescribed medication regularly as a result of chronic renal failure at primary and secondary medical care in Korea. Data were analyzed using t-test, ANOVA, Pearson correlation coefficients, and multiple regression. Results: There were statistically significant differences in medication adherence according to living area (p=.002), health condition (p<.001), amount of medication (p=.004), inconvenience for taking medication (p<.001), and depression level (p=.001). The mean of medication adherence was 3.72 points. Medication adherence was explained by perceived barrier related to medication taking (β=.338), attitude (β=.250), and depression (β=.132). Conclusion: This study strongly recommended that nursing intervention program to improve medication adherence should be developed and a match control study in improvement of medication adherence for hemodialysis patients needs to be done.